Investigation of tritium assimilation by sunflower crop at uptake through root - Polivkina, Ye.N.; Subbotina, L.F.; Zhamaldinov, F.F. (Fundamental and Experimental Biology, 2022)
This study presents a quantitative assessment of tritium assimilation by sunflower (Helianthus annuus L.) crop at HTO uptake by root in vitro. It is found that at chronic uptake of tritium radionuclide as tritiated water (HTO) by sunflower through root system mean value of OBT/TFWT ratio during vegetation was 0.21. The conversation rate of tissue free water tritium (TFWT) to organic matter as organically bound tritium (OBT) varied from 0.08 to 0.044 % h–1, with a maximum in the leafage phase. Translocation index (TLI) for sun-flower crop at root uptake of tritium was 65 %. The distribution nature of tritium in sunflower parts at lasting root uptake of tritium for tissue free water tritium and organically bound tritium decreases in the next rows consequently: “roots>inflorescences>stems>leaves” and “inflorescences>stems>leaves>roots”. At root up-take of tritium by sunflower as HTO form values of TFWT activity closely correlate with the activity of the isotope in water using for plant irrigation (r= 0.89). Established regularities of tritium assimilation and distri-bution in sunflower parts and OBT/TFWT ratio are of practical importance to biomonitoring of environmen-tal contamination with tritium at impact territories of nuclear fuel cycle enterprises.